2020
DOI: 10.1101/2020.06.15.152207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal firing in the medial temporal lobe reflects human working memory workload, performance and capacity

Abstract: Significance 15Humans are highly limited in processing multiple objects over a short period of time. 16The capacity to retain multiple objects in working memory is typically associated with 17 frontal and parietal lobe functioning, even though medial temporal lobe (MTL) neural 18 architecture seems capable to process such information. However, there are 19 conflicting findings from patient, electrophysiological and neuroimaging studies. Here 20 we show for the first time that correct performance, workload and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…We have reported earlier (Boran et al, 2020b ) that for the same task in the same subjects, we found neurons in the MTL that fired persistently and increased their firing rate for trials with a high workload during the maintenance period. Neuronal population firing in the MTL during maintenance distinguished workload and we could decode workload of single trials.…”
Section: Methodssupporting
confidence: 72%
See 4 more Smart Citations
“…We have reported earlier (Boran et al, 2020b ) that for the same task in the same subjects, we found neurons in the MTL that fired persistently and increased their firing rate for trials with a high workload during the maintenance period. Neuronal population firing in the MTL during maintenance distinguished workload and we could decode workload of single trials.…”
Section: Methodssupporting
confidence: 72%
“…For the selection of data, we build on earlier studies where we asked patients to perform cognitive tasks while we recorded iEEG. In these earlier studies, we recorded and associated the firing of single neurons with task performance, thereby confirming that the tasks were indeed activating regions of the MTL in the patients of this study (Boran et al, 2019a , 2020b ). The datasets are published for re-analysis (Boran et al, 2019b , 2020a ; Dimakopoulos et al, 2020 ; Fedele et al, 2020a , 2021 ).…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations